Annual and semi-annual temperature oscillations in the northern hemisphere - ASNANI , G.C.; VERMA, R. K. (MAUSAM, 1977)
1000-850mb and 1000-300 mb mean monthly thicknesses have been subjected to hormonic analysis at about 200 stations in the northern hemisphere. Salient features of the annual mean, the annual oscillation and the semi-annual oscillation are presented, It is shown that the heat low which appears over southeast Asia during the Summer monsoon is partly due to the permanent warm temperature over this region. In the annual oscillation, largest amplitudes occur at about the same place and at about the same time in the entire troposphere. It is shown that the annual oscillation of tropospheric temperature over southeast Asia is not spectacularly different from that over the rest of the northern hemisphere in the same latitudes. It is, therefore, suggested that the special features of the annual monsoon of southeast Asia are due to special permanent features of temperature (and associated pressure and wind) field over the area rather than due to very special features of the annual temperature oscillation over the area.